Editor's Choice – Volume–Outcome Relationships in Elective Abdominal Aortic Aneurysm Surgery: Analysis of the UK Hospital Episodes Statistics Database for the Getting It Right First Time (GIRFT) Programme. (October 2020) - Gray, William K.; Day, Jamie; Horrocks, Michael
Abstract : Objective: To investigate whether a volume–outcome relationship exists for elective abdominal aortic aneurysm (AAA) surgery conducted within the National Health Service (NHS) in England. Methods: This was an analysis of administrative data. Data were extracted from the Hospital Episodes Statistics database for England from April 2011 to March 2019 for all adult admissions for elective infrarenal AAA surgery. Data were extracted for the NHS trust and surgeon undertaking the procedure, the surgical technique used (open or endovascular), the financial year of admission, length of hospital and critical care stay during the procedure and subsequent emergency re-admissions (primary outcome) and deaths within 30 days. Multilevel modelling was used to adjust for hierarchy and confounding. Results: A dataset of 31 829 procedures (8867 open, 22 962 endovascular) was extracted. For open surgery, lower trust annual volume was associated with higher 30 day emergency re-admission rates and higher 30 day mortality. For open surgery, lower surgeon annual volume was associated with higher 30 day mortality and length of hospital stay greater than the median. For endovascular surgery, lower surgeon annual volume was associated with not having an overnight stay in critical care. None of the other volume–outcome relationships investigated was significant. Conclusion: For elective infrarenal AAA surgery in the UK NHS, there was strong evidence of a volume–outcome relationship for open surgery. However, evidence for a volume–outcome relationship is dependent on the specific procedure undertaken and the outcome of interest.